Impact of liquidity and Management Efficiency on profitability - Azhar, Syed (Journal of Entrepreneurship, Business and Economics, 2015)
This study investigated the impact of liquidity and management efficiency on profitability of select power distribution utilities in India. The study consist a sample of 23 power distribution utilities operating in India for the period of 2004-05 until 2013-14. Therefore the total panel (balanced) observations are 230. The return on capital employed is used as a measure for profitability explaining dependent variable, whereas a current ratio, quick ratio, absolute cash ratio, debtor turnover ratio, creditor turnover ratio, collection efficiency, interest coverage ratio are representing independent variable. Statistical tools such as Generalized Least Squares (GLS) regression are applied. The study found that debtor’s turnover ratio, collection efficiency and interest coverage ratio are showing a significant impact while quick ratio, absolute liquid ratio and creditor’s turnover ratio show an insignificant impact on the profitability of select sample utilities. Research paper Reference to this paper should be made as follows: Azhar, S. (2015). “Impact of liquidity and Man-agement Efficiency on profitability: An Empirical Study of Selected Power Distribution Utilities in India”, Journal of Entrepreneurship, Business and Economics, Vol. 3, No. 1, pp. 31–49.